(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
This study aims to investigate whether higher education can work as a vehicle of empowerment to eradicate poverty. It is based on fieldwork research at the Great Lakes Regional College (GLRC) in the Kanungu district of Uganda. The results depict a complex socio-economic image produced by poverty reduction policies. It is surprising, interrelated with various factors, and thus difficult to simply categorize as positive or negative. In the eyes of the institution’s founder, achieving poverty relief with regard to alumni career development remains a significant challenge. In fact, the school’s intended goal of creating a better future for college students is undermined by environmental constraints. With regard to the impact that the GLRC has had on the surrounding community since its establishment, this study’s findings indicate that simply providing higher education is insufficient to achieve community development. However, the GLRC’s role goes beyond that of a simple educational institution. Because it attracts an external population, the college serves as a multifunctional institution that triggers community changes at various levels. Taken together, this study offers potential directions for higher education institutions that target community development, and recommends a broad functional approach for such institutions.